Speed monitoring system using GSM Wireless Cellular Modems / Mustafa Kamal Basha Omar Basha - Omar Basha, Mustafa Kamal Basha (2014)
This paper describes a methodology for top-down design, model, MPLAB programmer, hardware design, block diagram of design, digital cellular technology used for transmitting and receiving mobile voice and services using GSM modems.